FORMULASI HUKUM TERHADAP PELAKU PERKOSAAN DENGAN PRIA SEBAGAI KORBAN - Aldi Rasyid Ilmar, (2021)
Rape in article 285 of the Criminal Code which states that "Anyone with violence or threats of violence forces a woman to have sex with him outside of marriage, is threatened with rape with a maximum imprisonment of twelve years". However, this article uses the vocabulary of "women" which makes this article weak if the victim is a man. Rape is the highest sexual violence and needs to be regulated further. Improving the vocabulary of "women" in article 285 can have a very good impact in protecting human rights. The problem approach used by the author is (Comparative Approach). Comparative law is an activity to compare the laws of one country with the laws of other countries. In this paper, the chosen countries are countries that have similarities with Indonesia, which are countries based on written regulations as the main source, such as France, the Netherlands and countries that have cultural similarities with Indonesia such as Malaysia. The ratification of the PKS Bill and the RKUHP can make the basis for law enforcement in Indonesia, especially regarding rape whose victims can be women or men, more perfect than before.